An Improved Threshold-Sensitive Stable Election Routing Energy Protocol for Heterogeneous Wireless Sensor Networks - Liquan Zhao; Qi Tang (Information, 2019)
In the Threshold-Sensitive Stable Election Protocol, sensors are randomly deployed in the region without considering the balanced energy consumption of nodes. If a node that has been selected as a cluster head is located far away from the base station, it will affect the efficiency of the network due to its early death. This paper proposes an improved energy efficient routing protocol named Improved Threshold-Sensitive Stable Election protocol (ITSEP) for heterogeneous wireless sensor networks. Firstly, we use a node state transformation mechanism to control the number of cluster heads in high-density node areas. Secondly, the proposed protocol improves the threshold formula by considering the distance from the node to the base station, the number of neighbor nodes, its residual energy, and the average distance between nodes. In addition, an optimal route with minimum energy consumption for cluster heads has been selected throughout data transmission. Simulation results show that this algorithm has achieved a longer lifetime than the stable election protocol algorithm, modified stable election protocol algorithm, and threshold-sensitive stable election protocol algorithm for the heterogeneous wireless sensor network.